1997
DOI: 10.1074/jbc.272.28.17473
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylethanolamine, a Biomarker of Phospholipid Modification during the Maillard Reaction in Vivo

Abstract: N⑀ -(Carboxymethyl)lysine (CML) is a stable chemical modification of proteins formed from both carbohydrates and lipids during autoxidation reactions. We hypothesized that carboxymethyl lipids such as (carboxymethyl)phosphatidylethanolamine (carboxymethyl-PE) would also be formed in these reactions, and we therefore developed a gas chromatography-mass spectrometry assay for quantification of carboxymethylethanolamine (CME) following hydrolysis of phospholipids. In vitro, CME was formed during glycation of diol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 29 publications
5
95
0
1
Order By: Relevance
“…The data suggest that hyperglycemia in diabetic patients does not affect AGE-PE concentrations in erythrocytes and plasma, whereas the Amadori-PE concentration was markedly increased under hyperglycemic conditions. Similar to the present results, Requena et al ( 12 ) reported that no differences were observed in erythrocyte CM-PE levels between healthy and diabetic subjects. The reason given was that the diabetic patients participating in that study were free of complications ( 12 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The data suggest that hyperglycemia in diabetic patients does not affect AGE-PE concentrations in erythrocytes and plasma, whereas the Amadori-PE concentration was markedly increased under hyperglycemic conditions. Similar to the present results, Requena et al ( 12 ) reported that no differences were observed in erythrocyte CM-PE levels between healthy and diabetic subjects. The reason given was that the diabetic patients participating in that study were free of complications ( 12 ).…”
Section: Discussionsupporting
confidence: 82%
“…For the occurrence of AGE of PE in vivo, there have been at least three confl icting reports (12)(13)(14). Requena et al ( 12 ) and Pamplona et al ( 13 ) detected hydrolysis product of CM-PE in the acid hydrolysates of human erythrocyte and mammalian mitochondrial phospholipids using GC-MS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is conceivable that the frequent intake of dietary § Lin, J., Alt, A., Liersch, J., Reinhard, G. B., Brownlee AGE promotes a sustained low-grade inf lammatory state. In this sense, other markers of immune response such as cytokines and adhesion molecules are inducible by AGEs via reactive oxygen species production and nuclear factor B activation (7)(8)(9)(10)(11)(12)(13)(14)44), properties which are also exhibited by dietary AGEs (25). These reactive molecules (ranging between 12 and 22 million AGE units in a ''healthy meal''), which are ''seeding'' the systemic circulation regularly, could, together with hyperglycemia, contribute to the subtle inf lammatory state associated with diabetes (23,(41)(42)(43)45).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of pathogenic AGEs is not known as yet (10)(11)(12), and multiple derivatives other than those of MG or CML moieties have yet to be identified. Immunoreagents to MG derivatives and CML-like products, however, have presented invaluable means for animal and clinical correlations (10,11,24,25).…”
mentioning
confidence: 99%
“…2A). The nitrogen of the adjacent monomer unit then engages in a second cyclization through a six-membered transition state to form diketopiperazine 2, the dimer of a known metabolite (hydroxyethyl glycine) of the Maillard reaction (44). Although slow at low pH, this rearrangement is exceptionally fast and efficient at pH 7.4; homooligomers degrade with a half-life of 2 min (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%